Figuration et esthétique de l’identité génétique : autour de l’Autoportrait génétique de Gary Schneider - Samson, Hélène (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2008)
This article considers the ways artists interpret the phenomena of genetic identity through portraiture. After a survey of genetic iconography, it concentrates on the Genetic Self-Portrait (1997) of Gary Schneider. This portrait contains fifty-five black-and-white photographs showing Schneider's own chromosomes, DNA, and several highly individualized body parts such as hand, ear, iris, and sperm. Most of these fragments have been registered with technological medical devices. Critics have underlined the sublime in the genetic aesthetic carried in Schneider's prints. They also have acknowledged the recurrence of mythic and religious beliefs in the genetic aesthetic. Moreover, considering genetic identity, critics have raised the issues of predicting one’s biological future and of tracing one’s ethnic origin. The author argues that Schneider’s Genetic Self-Portrait pushes the logic of the ID portrait paradigm by replacing the face with genetic identifiers and by maintaining the scientific quality of photography. It is also shown that the genetic portrait entails a “double-bind” relationship because it involves a contradiction between the expected resemblance of portraiture and the genetic features in which the model cannot recognize himself. But in return, in Schneider's prints, this portrait-with-out-face offers associative and narrative possibilities that solve the paradox. The rhetoric of Schneider’s self-portrait alludes to an already known conception of the human being in a cosmological view that emphasizes sexuality and hereditary transmission. The genetic portraits of Kevin Clarke, Inigo Manglano-Ovalle, and Marc Quinn are also considered for their different approaches to genetic identity.